2018
DOI: 10.1101/335794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energy conservation via hydrogen cycling in the methanogenic archaeonMethanosarcina barkeri

Abstract: word count: 208 16Importance word count: 88 17 Main text word count: 3579 18 19All rights reserved. No reuse allowed without permission.(which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…More recent models propose that two electron transfer routes from lactate to sulfate operate simultaneously: the pathway of the hydrogen cycling model including the transient production and consumption of H 2 , and a second H 2independent pathway involving a direct electron transfer from the donor to the acceptor ( Figure 2) (Keller & Wall, 2011;Noguera, Brusseau, Rittmann, & Stahl, 1998;Sim et al, 2013). In the methanogenic archaeon Methanosarcina barkeri, Kulkarni et al have very recently demonstrated, thanks to a series of hydrogenase mutants, the role of H 2 cycling in energy conservation and proposed, based on the common occurrence of both cytoplasmic and periplasmic hydrogenases, that this mechanism may be widespread in nature, especially among anaerobic microorganisms (Kulkarni, Mand, & Metcalf, 2018).…”
Section: Different Models For the H 2 Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent models propose that two electron transfer routes from lactate to sulfate operate simultaneously: the pathway of the hydrogen cycling model including the transient production and consumption of H 2 , and a second H 2independent pathway involving a direct electron transfer from the donor to the acceptor ( Figure 2) (Keller & Wall, 2011;Noguera, Brusseau, Rittmann, & Stahl, 1998;Sim et al, 2013). In the methanogenic archaeon Methanosarcina barkeri, Kulkarni et al have very recently demonstrated, thanks to a series of hydrogenase mutants, the role of H 2 cycling in energy conservation and proposed, based on the common occurrence of both cytoplasmic and periplasmic hydrogenases, that this mechanism may be widespread in nature, especially among anaerobic microorganisms (Kulkarni, Mand, & Metcalf, 2018).…”
Section: Different Models For the H 2 Metabolismmentioning
confidence: 99%
“…This endergonic reduction is driven by the electrochemical proton potential (Forzi et al, 2005;Hedderich, 2004) ( Figure 5B). It has recently been demonstrated that Methanosarcina barkeri is capable of energy conservation via H 2 -cycling thanks to two H 2 -producing cytoplasmic hydrogenases, among them is Ech, and a H 2oxidizing periplasmic hydrogenase (Kulkarni et al, 2018). In Thermoanaerobacter tengcongensis (now Caldanaerobacter subterraneus subsp.…”
Section: The Ech Hydrogenasementioning
confidence: 99%